Faktor-Faktor yang Mempengaruhi Perilaku Auditor dalam Penghentian Prematur atas Prosedur Audit - Astia Putriana; Novita Weningtyas Respati; Chairina Chairina (Journal of Accounting and Investment, 2015)
The purpose of this research is to examine the effect of time pressure, audit risk, materiality, review procedure and quality control, need for achievement, and professional commitments on the auditor in premature termination on audit procedures. This reseach applies a mail survey as data collection method and convienece sampling as sample collection method. Research subjects are 106 auditor at the Supreme Audit Board of the Republic of Indonesia (BPK RI) Representative of South Kalimantan and Central Kalimantan. Empirical evidence finds that audit risk effect toward premature termination on the audit procedures. However, time pressure, materiality, review procedure and quality control, need for achievement and professional commitment does not effect toward premature termination on the audit procedures.